IMMUNOLOGICAL ASPECTS OF KIDNEY DAMAGE IN POST-COVID PATIENTS - Mirakhmedova H. T.; Khudaybergenova D. H. (Modern American Journals, 2025)
The article highlights considerations related to the emergence of COVID-19 and its spread in the world, challenges for medical workers, rapid diagnosis of infection, provision of specialized medical care, and prevention of complications. The article also reflects an analysis and consideration of modern approaches to the clinical and pathogenetic features of the epidemiology of the disease, complications, and diagnosis.
Keywords: COVID-19, type 2 diabetes mellitus, interleukin, chronic kidney disease